2021
DOI: 10.1093/jn/nxab030
|View full text |Cite
|
Sign up to set email alerts
|

Household Water and Food Insecurity Are Positively Associated with Poor Mental and Physical Health among Adults Living with HIV in Western Kenya

Abstract: Background Household food insecurity (FI) and water insecurity (WI) are prevalent public health issues that can co-occur. Few studies have concurrently assessed their associations with health outcomes, particularly among people living with HIV. Objectives We aimed to investigate the associations between FI and WI and how they relate to physical and mental health. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 65 publications
3
28
0
Order By: Relevance
“…Problems with water are common in regions with high HIV prevalence (e.g., sub-Saharan Africa), although few studies have considered both conditions concurrently [6][7][8]. Understanding the relationship between water insecurity, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Problems with water are common in regions with high HIV prevalence (e.g., sub-Saharan Africa), although few studies have considered both conditions concurrently [6][7][8]. Understanding the relationship between water insecurity, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Water insecurity is distinct from, but related to, food insecurity (i.e., the inability to access sufficient nutritious foods) and poverty [6,7,[10][11][12]. Food insecurity is a critical social determinant of health, including HIV-related clinical outcomes [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Inadequate WASH and food insecurity has been linked to poorer physical health [ 6 ]. Increasingly however, using untreated drinking water in low- and middle-income countries (LMICS) has been found to impact mental health by increasing depression and anxiety [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The first cross cultural and ecological household water security index includes 12 measures three of which are connexion to emotional issues of anger, worry and shame (Young et al, 2018(Young et al, , 2019. Recent research has shown the influence of household water insecurity on mental disorders, such as depression and anxiety (Brewis et al, 2019;Miller et al, 2021).…”
Section: Introductionmentioning
confidence: 99%